2015
DOI: 10.1016/j.pdpdt.2014.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Low-level light therapy potentiates NPe6-mediated photodynamic therapy in a human osteosarcoma cell line via increased ATP

Abstract: Background Low-Level Light Therapy (LLLT) is used to stimulate healing, reduce pain and inflammation, and preserve tissue from dying. LLLT has been shown to protect cells in culture from dying after various cytotoxic insults, and LLLT is known to increase the cellular ATP content. Previous studies have demonstrated that maintaining a sufficiently high ATP level is necessary for the efficient induction and execution of apoptosis steps after photodynamic therapy (PDT). Methods We asked whether LLLT would prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 32 publications
1
25
0
1
Order By: Relevance
“…B). However, in vitro studies showed that PBM can increase ATP production and increase the expression of mitochondrial benzodiazepine receptors, thereby promoting mitochondrial PpIX synthesis that may enhance the phototoxicity of PDT . We did not investigate if PBM altered the cellular PpIX distribution, but PBM did not appear to increase PpIX synthesis as the median total amount of skin surface PpIX fluorescence was similar between skin exposed to PBM and placebo‐PBM.…”
Section: Discussionmentioning
confidence: 91%
“…B). However, in vitro studies showed that PBM can increase ATP production and increase the expression of mitochondrial benzodiazepine receptors, thereby promoting mitochondrial PpIX synthesis that may enhance the phototoxicity of PDT . We did not investigate if PBM altered the cellular PpIX distribution, but PBM did not appear to increase PpIX synthesis as the median total amount of skin surface PpIX fluorescence was similar between skin exposed to PBM and placebo‐PBM.…”
Section: Discussionmentioning
confidence: 91%
“…2 Time to local recurrence some recent ex vivo experiments suggest a possible adverse effect of PBM on head/neck cancer cell [21]. Actually, some recent laboratory observations suggest that PBM might sensitize cancer cells to radiation [22] or increase apoptosis [23], both being potentially promising strategies that could be applied in the clinic.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, Schartinger et al [91] observed a pro-apoptotic effect of PBM in head and neck SCC cells, whereas no anti-apoptotic effects occurred that might promote tumor cell resistance to cancer therapy. Increased apoptosis of human osteosarcoma cells was also induced by the administration of NIR (810 nm, continuous wave, 20 mW/cm 2 , 1.5 J/cm 2 ) prior to NPe6-mediated photodynamic therapy as a result of increased cellular ATP and a higher uptake of the photosensitizer [92]. Recently, it was reported that PBM administered to normal human lymphoblasts and leukemia cells prior to RT, resulted in a differential response of normal versus malignant cells suggesting that PBM does not confer protection and may even sensitize cancer cells to RT-induced killing [93].…”
Section: Protective Effects Of Pbm Against Cytotoxic Therapymentioning
confidence: 99%